Auditoria interna diante do paradigma da flexibilização organizacional - Yokemura, Fernando Hideyo (2001)
The great challenge, in terms of human factor, related to the planning of the strategy of an organization is to integrate the sides human and managerial through mechanisms that make possible the appropriate control of the activities, in a such way that the company obtains won developing and being developed by your collaborators. In the last decades the world of the work is suffering several mutations. If in a high level he/she enrolls a pressure for the globalization of the economical activity of new markets; in a low level, the resource is observed to the economical efficiency as guiding criterion of the new employment politics, the alteration of the constitution of the manpower and a growing pressure for the organizational flexibilization as competitive factor. These are some of the changes that have been leading to the appearance of new social inequalities in the world of the work and that have been coming to affect the workers' implication organizational being translated then in the emergency of new values, expectations, and evaluations face to the work and the established relationship between the individuals and the organizations. Before that perspective, the elaboration of the present work had as objective approaches the effects of an audit it interns before the paradigm of the organizational flexibilization. It evaluates if the concepts of the internal audit and your performance, in a bank atmosphere, are just centred in the internal controls or if in some way they contribute inside to the democratization of the social relationships of the organization. We concluded the work exploring the internal auditor's fundamental paper and your potential for use of the instrument democratization of the social relationships in the organizations.